A 3D Modulation Scheme for High-speed Baseband Digital Communication System. Issue 1 (1st March 2022) - Feng, Yeqing; Lai, Zhengrong; Zhu, Fusheng; Hu, Zemin
Abstract: To improve the transmission rate of wireless communications, the communication frequency band will gradually go higher, and the use of millimeter wave and terahertz will become mainstream in the future. However, the signal attenuation in high bands is considerable, which prevents the achievement of long-distance transmissions. In this paper, we propose a 3D modulation scheme that is especially suitable for high-speed baseband digital communication systems. The proposed scheme is simulated and tested in an experiment. With the same order of modulation, the 3D modulation shows a significant decrement in bit error rate and enables a longer transmission distance.